Evaluating the Biophysical Resource Management Strategies of the Agro-ecosystems in Farm Communities of the Mantaro Valley, Central Andes of Peru - García Bendezú, Sady Javier (2011)
Abierto en el repositorio institucional de la Katholieke Universiteit Leuven: https://lirias.kuleuven.be/1716993